VARIABILITY OF MULTIPLE INTERPRETATIONS OF LOCATIVE-TEMPORAL CHARACTERISTICS OF A MEDIA EVENT - S. V. Mokhireva (Вестник Кемеровского государственного университета, 2015)
The article describes one of the factors influencing the interpretation of events in the media. The process of verbalization creates a cognitive model of the event, which is projected in a variety of media texts on the lexical and grammatical level. Locative-temporal characteristics represent one of the aspects by which the potential variability of interpretations of a reality fragment manifests itself.